The influence of audit quality on real earnings management: Do leverage and cash flow matter? - Lien Quynh Le (Journal of Economics and Development)
Purpose – This study examines how financial leverage and cash flow influence the relationship between audit quality and real earnings management. Design/methodology/approach – We analyze data from 499 non-financial firms listed on the Vietnam stock market between 2008 and 2023. The study uses the Roychowdhury (2006) model to assess real earnings management and applies OLS, FEM, and GLS regressions. Findings – The results indicate that audit quality influences real earnings management differently depending on a firm’s financial condition. Specifically, higher audit quality is associated with lower levels of real earnings management in firms with sufficiently low financial leverage and sufficiently high operating cash flows. However, audit quality is positively related to real earnings management for firms with sufficiently high leverage and sufficiently low or negative cash flows. Originality/value – This study offers a new insight into the impact of audit quality on real earnings management. Contributing to the agency theory, this study emphasizes the critical role of the firm’s financial condition in shaping the relationship. This study argues that a firm’s internal financial condition may affect its outside monitoring effectiveness, such as audit quality, in limiting the inherent conflicts of interest between managers and shareholders.